The analysis of the L. Padilla Mental Ability Test as an admission tool at the U.P. Iloilo College High School - Jesena, Felicidad Hernandez 1925-
This paper analyzes the L. Padilla test to determine if it can be used as a predictor device for the admissions function at the UP Iloilo College High School. Findings show that the L. Padilla test can be one of the valuable tools of admission at the Iloilo College High School, UP if the items found to be very difficult are to be changed and those with low discriminative power are to be reconstructed.